2008
DOI: 10.1002/ps.1598
|View full text |Cite
|
Sign up to set email alerts
|

Biocompost from sugar distillery effluent: effect on metribuzin degradation, sorption and mobility

Abstract: Biocompost from sugarcane distillery effluent can be used effectively to reduce downward mobility of metribuzin in low-organic-matter sandy loam soil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 25 publications
0
7
0
3
Order By: Relevance
“…However, determining the behavior of herbicides in soil amended with nonchemical fertilizers is difficult. Some researchers reported that the application of organic-based fertilizers under different situations increases the herbicide degradation and movement in soil and under other conditions may decrease them (Singh 2008;Fernandez-Bayo et al 2009;Kravvariti et al 2010). The effects of non-chemical fertilizers on removal and sorption of pesticides have been extensively studied and different results have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, determining the behavior of herbicides in soil amended with nonchemical fertilizers is difficult. Some researchers reported that the application of organic-based fertilizers under different situations increases the herbicide degradation and movement in soil and under other conditions may decrease them (Singh 2008;Fernandez-Bayo et al 2009;Kravvariti et al 2010). The effects of non-chemical fertilizers on removal and sorption of pesticides have been extensively studied and different results have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…These results in natural soils are in agreement with the previous reports, which suggested that soil OC content greatly affect the metribuzin sorption in soils. [20] However, K f values for metribuzin desorption in these soils followed the order: soil 2 > soil 3 > soil 1, thus maximum desorption of metribuzin was observed from soil 1 and the minimum from soil 3. This suggests that soil OC was not the only factor affecting the sorption of metribuzin.…”
Section: Resultsmentioning
confidence: 93%
“…Studies of adsorption and desorption normally include descriptive analyses of the data without using statistical tests to compare the k f , k d , and n values (ANDRADE et al, 2010;BARIZON et al, 2006;MAJUMDAR;SINGH, 2007;SINGH, 2008;SONG et al, 2008;ZHAOHAI et al, 2008). For the adsorption data in our study, ANOVA was used with a completely randomized design to compare the means of k f(s) and k d(s) for the two treatments using Tukey's Test (5% significance).…”
Section: Adsorption and Desorption Assaymentioning
confidence: 99%
“…Furthermore, most studies have added organic matter to soil in the form of solid waste such as sewage sludge (SONG et al, 2008), biocompost from sugar distillers (SINGH, 2008), rice straw (JIANG et al, 2008) and cow manure (DORADO et al, 2005) as well as with commercial organic fertilizer (LI et al, 2005). Few studies have examined the use of wastewater, which is characterized by the presence of large amounts of dissolved organic matter (MULLER et al, 2007).…”
Section: Introductionmentioning
confidence: 99%